2021
DOI: 10.3390/ijms222112083
|View full text |Cite
|
Sign up to set email alerts
|

Translation Inhibitors Activate Autophagy Master Regulators TFEB and TFE3

Abstract: The autophagy-lysosome pathway is a major protein degradation pathway stimulated by multiple cellular stresses, including nutrient or growth factor deprivation, hypoxia, misfolded proteins, damaged organelles, and intracellular pathogens. Recent studies have revealed that transcription factor EB (TFEB) and transcription factor E3 (TFE3) play a pivotal role in the biogenesis and functions of autophagosome and lysosome. Here we report that three translation inhibitors (cycloheximide, lactimidomycin, and rocaglam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 90 publications
2
8
0
Order By: Relevance
“…Because of the critical role of autophagy in protein degradation and the subsequent recycling of amino acids for the upkeep of protein synthesis, a growing number of studies have focused on the association between autophagy and translation. Dang et al found that translation inhibitor-mediated translation shutoff promoted autophagosome biogenesis but blocked the formation of degradative autolysosomes by destroying functional lysosomes ( 57 ). Similar phenomena have also been observed during bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the critical role of autophagy in protein degradation and the subsequent recycling of amino acids for the upkeep of protein synthesis, a growing number of studies have focused on the association between autophagy and translation. Dang et al found that translation inhibitor-mediated translation shutoff promoted autophagosome biogenesis but blocked the formation of degradative autolysosomes by destroying functional lysosomes ( 57 ). Similar phenomena have also been observed during bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…TFE3 regulates metabolism by directly regulating autophagy depending on the nutritional status of the cell Several studies have revealed that TFE3 is a key regulator of autophagy and that autophagy is closely associated with the metabolic regulation of cells [82,83]. Metabolism regulation via autophagy is primarily achieved through the mammalian target of the rapamycin 1(mTOR1) pathway [84].…”
Section: Tfe3 Regulates Cell Metabolism By Enhancing Lysosomal Activi...mentioning
confidence: 99%
“…Autophagy and mTOR signaling pathways regulate cell metabolism during cell starvation and adequate nutritional conditions, respectively. TFE3 primarily enhances cell metabolism [82,83,96]. In general, TFE3 activates autophagy only when the mTOR signaling pathway is inactivated [5].…”
Section: Tfe3 Regulates Cell Metabolism By Enhancing Lysosomal Activi...mentioning
confidence: 99%
“…Autophagy is a cellular degradation process that delivers intercellular cargo to the lysosomes [30]. Autophagy can be triggered by cellular stress including nutrient deprivation and hypoxia [31]. Furthermore, autophagy can degrade long-lived proteins and organelles and recycle them to support cell survival [32].…”
Section: Introductionmentioning
confidence: 99%